Responsibilities And Werda Notary's Legal Protection for Deeds He Made While Still Serving as a Notary - Al Majid, Muchammad Bachtiar; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Responsibility and legal protection in the UUJN only regulates